Kolaborasi Budaya Batak Toba dengan Gereja HKBP - Mangihut Siregar; Ratna Ani Lestari; Ratih Kumala Dewi Lubis; Randy Rahadian Limanjaya (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The Batak tribe has several sub-tribes, namely, Toba, Mandailing, Pakpak, Angkola, Simalungun and Karo. Each sub-tribe has its own local church except the Mandailing Batak which joined the Angkola Batak. Of all the Batak sub-tribes, the Toba Batak is the most dominant sub-tribe compared to the others. Due to the large number of people from the Toba Batak sub-tribe, HKBP as the Toba Batak tribal church has the most people compared to other sub-tribes. Not only among the Batak sub-tribe, HKBP is also the largest church denomination in Southeast Asia. This research examines the collaboration between Toba Batak culture and the HKBP church. The research location was carried out in the overseas area and also the area of ​​origin of the Toba Batak sub-tribe. The research method used was qualitative. Data sources were obtained through interviews and literature studies. Data collection techniques in this research are by observation, interviews, literature study and document study. The theories used are postcolonial theory and hegemony theory. The research results show that Toba Batak culture is very collaborative with the HKBP church. On the other hand, the HKBP church is very collaborative with Toba Batak culture. Between culture and the HKBP church there is a relationship that is mutually supportive and mutually beneficial.